A Laboratory Dust Generator Applying Vibration to Soil Sample: Mineralogical Study and Compositional Analyses. Issue 7 (8th April 2020) - Qu, Z.; Trabelsi, A.; Losno, R.; Monna, F.; Nowak, S.; Masmoudi, M.; Quisefit, J.‐P.
Abstract: A laboratory study was carried out using a vibrating system (SyGAVib) to produce aerosols from four soils collected in the central Tunisian region around Sfax. The aim of this device is to mimic dust emission by natural wind erosion. Using compositional analysis, the dust produced was compared to (i) dust generated in a wind tunnel by the same soils, (ii) fine sieved and (iii) original bulk soils, and (iv) naturally occurring aerosol samples collected in the same area. The relative quartz content strongly decreases from bulk to fine soils, and again from fine soils to both wind tunnel and vibration‐generated aerosols. Compositional data analysis (CoDA) clearly shows (i) a silica dilution effect in bulk soils, and (ii) that if silica is removed from the composition, the elemental compositions of fine soils and generated aerosols are similar but differ from bulk soils. Both aerosol generation methods produce material with chemical compositions that are also close to those measured in field‐sampled aerosols, and the fine soil composition is much closer to that of field and laboratory aerosols than to the parent soil. Aerosols generated from soils in the laboratory, either using a vibrating system or a wind tunnel, can be used as surrogates of the particles collected directly in the field. Plain Language Summary: A laboratory study was carried out using a vibrating system (SyGAVib) to produce particles from four soils collected in the central Tunisian region around Sfax. The aim of this device is to mimic dust emission by natural wind erosion. The chemical composition of the dust produced was compared to another dust generator (a wind tunnel), fine‐sieved soil, original bulk soils, and finally naturally occurring dust found in the same area. Both dust generators produce similar samples which look very different from bulk soils. Key Points: Compositional analysis using biplots and Aitchison distance is a valuable tool for chemical variation comparisons Dust aerosol can be extracted from soil using vibrations as well as wind friction Figures of merit of a new small size dust generator system for fast extraction of dust from parent soil